IDIOPATHIC SPONTANEOUS POSTERIOR GASTRIC PERFORATION IN A PRESCHOOL CHILD---A RARITY - Prabhu, Vinod Varada; Prasadi, Sadanand; Dhanawade, Sarah (Journal of Postgraduate Medical Institute, 2012)
A three year old female presented in casualty with history of abdominal pain, vomiting abdominaldistension and dyspnoea. The patient was in shock and there was abdominal guarding all over.History was of a very short duration. Abdominal X- ray showed massive gas under diaphragm. Patient wasexplored which revealed a posterior large gastric perforation. The rest of organs showed no obviousabnormality. The biopsy was inconclusive, serum gastrin was normal with no hematological abnormality.The post operative period was uneventful.